White-skinned sweet potato (Ipomoea batatas L.) acutely suppresses postprandial blood glucose elevation by improving insulin sensitivity in normal rats. Issue 4 (April 2023) - Kinoshita, Akito; Nagata, Takuma; Furuya, Futoshi; Nishizawa, Mikio; Mukai, Eri
Abstract: Long-term administration of Ipomoea batatas L. (white-skinned sweet potato, WSSP) has been reported to help manage type 2 diabetes mellitus (T2DM) in humans and animals; however, the mechanisms of blood glucose regulation by WSSP remain unclear. Therefore, we aimed to investigate the acute effects of WSSP on blood glucose homeostasis under normal conditions and the underlying mechanisms. Three fractions of WSSP (≤10, 10–50, and >50 kDa) were obtained via ultracentrifugation. Rats were subjected to an oral glucose tolerance test (OGTT) after a single administration of WSSP. The insulin tolerance test (ITT) and pyruvate tolerance test (PTT) were performed to evaluate insulin sensitivity and gluconeogenesis, respectively. Single WSSP administration markedly reduced blood glucose levels as revealed by the OGTT. Serum insulin levels were not increased by WSSP treatment. Blood glucose levels during ITT were significantly reduced due to WSSP treatment. WSSP treatment activated the phosphorylation of Akt, thereby activating insulin signaling in the skeletal muscles and liver. The ≤10 kDa fraction considerably reduced blood glucose levels per the OGTT and ITT. In contrast, gluconeogenesis in PTT and the expression of key enzymes in hepatocytes were suppressed by the >50 kDa fraction. This study demonstrated that WSSP acutely reduced postprandial blood glucose levels by improving insulin sensitivity in skeletal muscles in normal rats, which was attributed to constituents with a molecular weight of ≤10 kDa. Moreover, WSSP treatment suppressed gluconeogenesis in the liver, for which constituents of >50 kDa were responsible. Thus, WSSP can acutely regulate blood glucose homeostasis via multiple mechanisms. Since postprandial hyperglycemia leads to the onset of T2DM, WSSP, as a functional food, may possess potential active compounds that prevent T2DM. Graphical abstract: Image 1 Highlights: WSSP suppressed postprandial blood glucose levels via improved insulin sensitivity. The ≤10 kDa fraction of WSSP improved glucose tolerance and insulin sensitivity. The >50 kDa fraction of WSSP suppressed gluconeogenesis both in vivo and in vitro . WSSP can exhibit hypoglycemic activity via multiple constituents in normal rats.